Răspuns :
Răspuns:
Explicație pas cu pas:
[tex]\frac{(\frac{9+7}{15})*\frac{6}{10} }{(\frac{14-3}{7})*\frac{25}{100} } =[/tex][tex]\frac{\frac{16}{15}*\frac{3}{5} }{\frac{11}{7}*\frac{1}{4} } =[/tex][tex]\frac{16}{25}*\frac{28}{11} =[/tex][tex]\frac{448}{275} =1\frac{173}{275}[/tex]
[tex] \frac{( \frac{3}{5} + \frac{7}{15} ) \times 0.6}{(2 - \frac{3}{7} ) \times 0.25} = \\ \frac{ \frac{16}{15} \times \frac{3}{5} }{ \frac{11}{7} \times \frac{1}{4} } = \\ \frac{ \frac{16}{5} \times \frac{1}{5} }{ \frac{11}{28} } = \\ \frac{ \frac{16}{25} }{ \frac{11}{28} } = \\ \frac{448}{275} [/tex]